112k views
3 votes
-2(x + 3) = -2x + 3 - 9

User Rumin
by
6.0k points

2 Answers

4 votes

Answer:

x = x

Explanation:

The first step here is to use the distributive property to make the first equation back into a polynomial.

The way we do this is by multiplying each term on the inside of the parentheses by the -2 on the outside.

-2 x x = -2x

-2 x 3 = -6

So, our new equation reads: -2x - 6

-2x - 6 = -2x + 3 - 9

Our next step is to subtract the 9 from 3.

-2x - 6 = -2x - 6

We add 6 to each side

-2x = -2x

x = x

0 = 0

User Ray Zhou
by
6.0k points
3 votes

Answer:

the answer is in the picture

Have a safe and happy new years

Explanation:

-2(x + 3) = -2x + 3 - 9-example-1
User Kklo
by
6.4k points